Sources of vibroacoustic hazards in open-pit mines of mineral raw materials - ENGEL, Jacek R.; KOSAŁA, Krzysztof (Archives of Acoustics, 2007)
Many sources of vibroacoustic energy manifest themselves in open-pit mines of mineral raw materials. Noise and vibrations are the reasons of occupational diseases and injuries at work. Exploitation of open-pit mines of minerals constitutes hazards not only at workstations but also for the natural environment.Kinds of noise sources depend on the technology applied in open cast mining. Noise levels often exceed the permissible values. Besides high noise levels, values of vibrations - general and local - which are the highest during processes of mining, loading and transporting are also significant. Among machines and devices used at raw material mining the highest noise is caused by crushers, dumping conveyers, bulldozers etc. Blasting works are the source of short-lived noises however, characterised by high levels of acoustic pressures.Identification of sources of vibroacoustic hazards occurring in one of the open-pit mine is presented in the paper. The obtained results of measurements of noise levels generated by sources of continuous and impulse noises are also given.